PERSYARATAN KECUKUPAN MODAL MINIMUM DAN PERILAKU BANK DI INDONESIA - Maromi Merlin Mbate (Akademi Akuntansi YKPN Yogyakarta, 2014)
This study aims to analyze the impact of bank capital requirements in Indonesia where credit and capital crunch. In investigating the impact of bank capital requirements, we set up a simple model of the banking firm as well as having possible effects on the economy. In this study, change of deposits and change of loan were included as the dependent variable and capital requirements as the independent variable while logarithm of total assets, Certificates of Bank Indonesia (SBI) and growth of GDP as the control variable. In estimation, we use annually panel data of all the banks conventional period 2002-2206 while number of samples was 372 banksyears. Based on our econometric tests, we choose the Fixed Effect panel regression model because the bank specific characteristics are found to be different. The results of this study indicated that regulatory capital takes part in the change of Indonesia banks behaviour. The main finding of this study, firstly from the liabilities side of banks is that there was a strong positive relationship between bank capital and growth rate of deposits, where the impact of change in capital is smaller for well-capitalised banks than for poor-capitalised banks. Secondly, with regards to bank lending, it was shown that credit crunch was less apparent in the aftermath of change in capital regulatory in Indonesia. Thus, this study supported of capital crunch. Keywords: Capital Adequacy Ratio, Deposits, Loans, Capital Crunch